The efficacy and safety of qiwei baizhu san in the treatment of type 2 diabetes mellitus: a systematic review and meta-analysis - Zhang, Quan; Liu, Hongyan; Zhang, Jiahong; Ouyang, Yujie; Fu, Xiaoxu; Xie, Chunguang (Frontiers in Pharmacology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia, mostly resulting from impaired insulin production and diminished glucose metabolism regulation. Qiwei Baizhu San (QWBZS) is a classic formula used in traditional Chinese medicine for the treatment of T2DM. A comprehensive analysis of the efficacy and safety of QWBZS in the treatment of T2DM is essential.MethodsThis study’s protocol was registered with PROSPERO (CRD42024576129). As of August 2024, we searched eight databases to screen and include randomized controlled trials of QWBZS for T2DM. Heterogeneity sources were examined via subgroup analyses, the robustness of the results was determined by sensitivity analyses, publication bias was evaluated using funnel plots and Egger’s test, evidence quality was appraised with GRADEpro, and possible mechanisms of QWBZS for T2DM were categorized and summarized.ResultsThis analysis encompassed 14 qualifying trials with a total of 1,169 subjects. The analytical results suggested that QWBZS, when combined with conventional treatment, was more effective than conventional treatment alone in improving FBG, 2hPG, HbA1c, HOMA-IR, TC, TG, LDL-C, and HDL-C. When QWBZS was used alone, it was more effective than conventional therapy in FBG, 2hPG, and HbA1c. And QWBZS could improve the overall effectiveness of clinical treatment in T2DM patients. The impact of QWBZS therapy alone on HOMA-IR and lipid metabolism remained unclear due to the limited number of trials included. Analysis of adverse events suggested that QWBZS was relatively safe.ConclusionThis study suggested that QWBZS, when combined with conventional treatment, was more effective in improving glucose metabolism, insulin resistance, and lipid metabolism compared to conventional treatment alone in individuals with T2DM. QWBZS alone also contributed to the regulation of blood glucose levels. Meanwhile, QWBZS could improve the overall effective rate of clinical treatment with a relatively high safety profile. Nevertheless, owing to the inferior quality and significant heterogeneity of the existing evidence, additional high-quality studies are requisite to furnish more dependable evidence for the future clinical application of QWBZS.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=576129, identifier [CRD42024576129].